INDIGENOUS KNOWLEDGE OF CATTLE KEEPING IN HADIYA ZONE, SOUTHERN ETHIOPIA - AYELE, WONDIMU; SHIBESHI, SAMUEL; ABREHAM, SELAMU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study was conducted to assess Indigenous Knowledge of Cattle Keeping in Hadiya Zone, Southern Ethiopia. Three districts (Shashogo, Misha and Soro) were purposively selected from each category. A total of 90 households owning cattle with 10 extension workers were selected randomly. There was significant (p<0.05) difference across the districts in livestock number per households. Hadiya people keep large size of herd considering it as a wealth, cultural and social security (mainly in Soro district).The motive behind the society is to secure the cultural title of ‘Tibima/Abegaz/Garad and Kumima’ which is attained in ascending order after achieving the first stage/title “Tibima/Garad” of possession of at least 100 cattle and the second, ’Kuma’’ title in which single individual can own more than 1000 cattle. The highest percent 91.7% of respondents in Shashogo and Soro, 85% of respondents in Misha keep cattle primarily for milk. The respondents revealed that cattle keepers, who dwell in low land areas, have the practices of allowing their cattle to scavenge and graze in early morning. This practice is locally named as ‘Waare’imma or waarechchaa’. The results of this study indicated that there is unexploited indigenous knowledge of cattle keeping in Hadiya Zone.